Pin loading effect on 3D spacer fabric-laminated composites produced vacuum infusion - Erdem, Sumeyye; Kaman, Mete O. (Sage Publications Ltd, 2022)
In this study, pin-loading behavior of laminated composites reinforced with three-dimensional (3D) spacer fabric was investigated, experimentally. Failure loads and modes of 3D-woven glass fiber epoxy composites, which are mostly preferred in automotive, machinery, and building production, are determined and compared with the mechanical properties of two-dimensional (2D)-woven fabric-reinforced composite materials. For this purpose, 2D plane and 3D spacer fabric composite plates were produced using the vacuum infusion method. The effect of pin geometry on joint strength and failure mechanism of composite was determined by tensile tests using test apparatus of single and two serial pin joint. In addition, low velocity impact tests of 2D and 3D plates were performed to explain the failure behavior. For mono-layer 3D-woven fabrics, the existence of out-of-plane fiber increases failure strength up to 50% compared to 2D fabrics. On the other hand, the use of multi-layer 3D fabric does not affect changes-specific failure load according to 2D fabrics significantly. Increasing in the specific load is only 9% for two-layers 3D. This situation has also been observed in impact tests.
Keywords: Laminated composites; pin joint; 3D spacer fabric; low velocity impact